A cross‐continental comparison of assemblages of seed‐ and fruit‐feeding insects in tropical rain forests: Faunal composition and rates of attack. (23rd March 2018) - Basset, Yves; Dahl, Chris; Ctvrtecka, Richard; Gripenberg, Sofia; Lewis, Owen T.; Segar, Simon T.; Klimes, Petr; Barrios, Héctor; Brown, John W.; Bunyavejchewin, Sarayudh; Butcher, Buntika A.; Cognato, Anthony I.; et al.
Abstract: Aim: Insects feeding on seeds and fruits represent interesting study systems, potentially able to lower the fitness of their host plants. In addition to true seed eaters, a suite of insects feed on the fleshy parts of fruits. We examined the likelihood of community convergence in whole insect assemblages attacking seeds/fruits in three tropical rain forests. Location: Three ForestGEO permanent forest plots within different biogeographical regions: Barro Colorado Island (Panama), Khao Chong (Thailand) and Wanang (Papua New Guinea). Methods: We surveyed 1, 186 plant species and reared 1.1 ton of seeds/fruits that yielded 80, 600 insects representing at least 1, 678 species. We assigned seeds/fruits to predation syndromes on the basis of plant traits relevant to insects, seed/fruit appearance and mesocarp thickness. Results: We observed large differences in insect faunal composition, species richness and guild structure between our three study sites. We hypothesize that the high species richness of insect feeding on seeds/fruits in Panama may result from a conjunction of low plant species richness and high availability of dry fruits. Insect assemblages were weakly influenced by seed predation syndromes, both at the local and regional scale, and the effect of host phylogeny varied also among sites. At the driest site (Panama), the probability of seeds of a plant species being attacked depended more on seed availability than on the measured seed traits of that plant species. However, when seeds were attacked, plant traits shaping insect assemblages were difficult to identify and not related to seed availability. Main conclusions: We observed only weak evidence of community convergence at the intercontinental scale among these assemblages. Our study suggests that seed eaters may be most commonly associated with dry fruits at relatively dry tropical sites where fleshy fruits may be less prevalent.